Combined determination of copper ions and β-amyloid peptide by a single ratiometric electrochemical biosensor. Issue 1 (1st December 2017) - Yu, Yanyan; Wang, Peng; Zhu, Xiaodan; Peng, Qiwen; Zhou, Yi; Yin, Tianxiao; Liang, Yixin; Yin, Xiaoxing
Abstract : A novel ratiometric electrochemical biosensor was developed for the combined determination of copper ion and β-amyloid peptide. Abstract : Copper ions (Cu 2+ ) play a critical role in biological processes and are directly involved in β-amyloid peptide (Aβ) aggregation, which is responsible for the occurrence and development of Alzheimer's disease (AD). Therefore, combined determination of Cu 2+ and Aβ in one analytical system is of great significance to understand the exact nature of the AD event. This work presents a novel ratiometric electrochemical biosensor for the dual determination of Cu 2+ and Aβ1–42 . This unique sensor is based on a 2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulphonate) (ABTS) and poly(diallyldimethylammonium chloride) (PDDA)-bi functionalized single-walled carbon nanotubes (ABTS-PDDA/CNTs) composite. The inclusion of ABTS not only enhanced the sensitivity, but it also acted as an inner reference molecule to improve detection accuracy. The specific recognition of Cu 2+ was realized by neurokinin B (NKB) coatings on the ABTS-PDDA/CNTs surface to form a [Cu II (NKB)2 ] complex with Cu 2+ . The ABTS-PDDA/CNTs-NKB modified electrode also displayed an excellent electrochemical response toward the Aβ1–42 monomer, when a certain amount of the Aβ1–42 monomer was added to Cu 2+ -contained PBS buffer, which was due to the release of Cu 2+ from the [Cu II (NKB)2 ] complex through Aβ binding to Cu 2+ . Meanwhile, our work showed that Cu 2+ bound Aβ1–42 was concentration-dependent. Consequently, the presented electrochemical approach was capable of quantifying two important biological species associated with AD by one single biosensor, with the detection limits of 0.04 μM for Cu 2+ and 0.5 ng mL −1 for Aβ1–42, respectively. Finally, the ratiometric electrode was successfully applied for monitoring Cu 2+ and Aβ1–42 variations in plasma and hippocampus of normal and AD rats.